FlowerNet: A Gene Expression Correlation Network for Anther and Pollen Development . Issue 4 (9th February 2015) - Pearce, Simon; Ferguson, Alison; King, John; Wilson, Zoe A.
Abstract : A network model of global transcriptional interactions, based on clustering of transcriptionally correlated genes using publicly available floral gene expression data sets, provides a community resource for studies of reproductive gene expression. Abstract: Floral formation, in particular anther and pollen development, is a complex biological process with critical importance for seed set and for targeted plant breeding. Many key transcription factors regulating this process have been identified; however, their direct role remains largely unknown. Using publicly available gene expression data from Arabidopsis ( Arabidopsis thaliana ), focusing on those studies that analyze stamen-, pollen-, or flower-specific expression, we generated a network model of the global transcriptional interactions (FlowerNet). FlowerNet highlights clusters of genes that are transcriptionally coregulated and therefore likely to have interacting roles. Focusing on four clusters, and using a number of data sets not included in the generation of FlowerNet, we show that there is a close correlation in how the genes are expressed across a variety of conditions, including male-sterile mutants. This highlights the important role that FlowerNet can play in identifying new players in anther and pollen development. However, due to the use of general floral expression data in FlowerNet, it also has broad application in the characterization of genes associated with all aspects of floral development and reproduction. To aid the dissection of genes of interest, we have made FlowerNet available as a community resource (http://www.cpib.ac.uk/anther ). For this resource, we also have generated plots showing anther/flower expression from a variety of experiments: These are normalized together where possible to allow further dissection of the resource.